TETANUS OUTCOMES IN ATERTIARY CARE HOSPITAL IN KARACHI. - Kiran Waqar1, Syeda Urooj Riaz2, Aijaz Ali3, Meraj Fatima4, Muhammad Ishaq5, Hani Sohail6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
Tetanus is a serious disease caused by a bacterial toxin that affects your nervous system, leading to painful muscle contractions, particularly of your jaw and neck muscles. Tetanus can interfere with your ability to breathe and can threaten your life. Tetanus is commonly known as "lockjaw. OBJECTIVE: "Our aim is to evaluate the frequency of different grades of tetanus and their outcome in patients of tetanus presenting to a tertiary care hospital in Karachi. METHODS: This is a descriptive observational study, conducted in Jinnah Medical College Hospital, Karachi. Duration of study was from 1st Jan, 2018 to 31st Dec, 2018. Patients with altered level of consciousness were excluded. Data was collected on predesigned Performa. Age was recorded as mean. Grading of tetanus was done according to clinical features using Ablett classification. Risk factors were stratified. RESULT: 48 (42 were male and 6 were female) patients were enrolled in the study during 1 year duration. The mean age of patients was 35 years. 35% patients were belonging to grade 4, 20.8 % grade 3, 33% grade 2 and only 10% belong to grade 1. The most common risk factor was trauma found in 22 (45.8%) patients while 13 (27%) patients had no risk factor for developing tetanus. 47.9% patients developed tetanus despite vaccinated while 25% patients did not know their immunization status. Overall mortality was 31% seen with grade 4. CONCLUSION: We should start proper awareness programs about its vaccination especially in emergency set up of every hospitals to overcome mortality and morbidity associated with it.